Multi-scale path planning for a planetary exploration vehicle with multiple locomotion modes - Sánchez, J. Ricardo; Azkarate, Martin; Pérez-del-Pulgar-Mancebo, Carlos Jesús (My University, 2018)
Planetary exploration vehicles (rovers) can encounter with a great variety of situations. Most of them are related to the terrain, which can cause the end of the mission if these vehicles are not able to traverse it. It was the case of Spirit rover, which got stuck in loose sand, making it impossible to continue advancing. A solution to this is to make rovers capable of modifying their locomotion to traverse terrains with particular terramechanic parameters.
Keywords: Robótica; Planning; Navigation; Rovers; Locomotion